2019
DOI: 10.1136/vr.105336
|View full text |Cite
|
Sign up to set email alerts
|

Association between results of diagnostic tests for bovine tuberculosis and Johne's disease in cattle

Abstract: BackgroundBovine tuberculosis (bTB) diagnosis is impaired by numerous factors including cross-reactivity with Mycobacterium avium subspecies paratuberculosis, which causes Johne’s disease (JD). In addition, the effect of repeated bTB-intradermal testing on the performance of JD diagnostic tests is not fully understood. This study aimed to evaluate the impact of repeated bTB-intradermal tests under field conditions in Spain on the JD serological status of cattle.MethodsbTB-positive herds (n=264) from Castilla-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 60 publications
(86 reference statements)
1
19
0
Order By: Relevance
“…The finding of a higher positive test rate for JD in herds that have bTB is similar to what is reported by Picasso-Risso et al, with a similar OR of 1.47 [ 27 ]. A herd history of bTB raises the odds for finding ‘high’ risk cows (OR = 1.2) but also puts a ceiling on the maximum possible length of bTB–JD testing interval.…”
Section: Discussionsupporting
confidence: 89%
“…The finding of a higher positive test rate for JD in herds that have bTB is similar to what is reported by Picasso-Risso et al, with a similar OR of 1.47 [ 27 ]. A herd history of bTB raises the odds for finding ‘high’ risk cows (OR = 1.2) but also puts a ceiling on the maximum possible length of bTB–JD testing interval.…”
Section: Discussionsupporting
confidence: 89%
“…Other factors not explicitly included in the study that could be related to increased duration of outbreaks include wildlife variables or the presence of concurrent infections compromising the diagnostic sensitivity. The effect of paratuberculosis in bTB diagnostic tests has been described in the past in Spain ( 5 , 55 , 56 ) and elsewhere ( 57 59 ). Similarly, cross-reactivity with environmental saprophytic mycobacteria could also artificially increase breakdown duration due to the presence of unspecific SIT reactions ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should be highlighted that in addition to M. bovis- infection, performing a TST can also influence MAP-positive results in tested animals. It is possible that TST could boost the antibody response and increase the sensitivity of paratuberculosis ELISA results [ 10 , 24 ]; this would indicate that at least some of the results were not false positives. However, the limited number of serological studies in Poland have found the seroprevalence of paratuberculosis in cattle to be much lower (1–3%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%